2017
DOI: 10.1002/cbe2.1040
|View full text |Cite
|
Sign up to set email alerts
|

Competency‐based education as a force for equity

Abstract: In recent publications, critics and advocates of competency-based education (CBE) have raised questions about whether or not CBE advances the cause of equity in education. This article offers a response, by way of a case study, describing an openadmissions CBE program for adult students with graduation rates over double the US national average. Exploring this program's success, the article argues that CBE can advance equity, but doing so requires research-based understanding of, institutionwide respect for,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…Evidence demonstrating the benefits of CBE was compelling. Research centered on adult learners suggested that CBE programs provide better social, academic, and professional outcomes for their students compared to traditional four-year pathways Navarre Cleary & Breathnach, 2017;. also found that because CBE programs are more directly associated with college and career readiness and flexible course pacing, CBE students show higher changes in intrinsic self-management, motivation, and cognitive control, which benefit them in situations and environments outside of the classroom setting .…”
Section: Cbe and Cpl Emerge In Research As Leading Practicesmentioning
confidence: 99%
“…Evidence demonstrating the benefits of CBE was compelling. Research centered on adult learners suggested that CBE programs provide better social, academic, and professional outcomes for their students compared to traditional four-year pathways Navarre Cleary & Breathnach, 2017;. also found that because CBE programs are more directly associated with college and career readiness and flexible course pacing, CBE students show higher changes in intrinsic self-management, motivation, and cognitive control, which benefit them in situations and environments outside of the classroom setting .…”
Section: Cbe and Cpl Emerge In Research As Leading Practicesmentioning
confidence: 99%
“…With this in mind, the design of direct assessment CBE programs was centered around equity and excellence. CBE programs are guided by a vision of equity in which education overcomes discrimination, oppression, bigotry, and biases that bar students from minoritized backgrounds, in particular adult learners, from gaining an education (Lopez et al, 2017). A focus on excellence helped determine the type of CBE programs to be offered and required a keen focus on student outcomes.…”
Section: De S I G Ning For Equ It Ymentioning
confidence: 99%
“…This is supported by findings by the American Institute for Research (AIR) which found that when students can directly align collegiate work with career readiness through a flexible course pace, they show improvements in intrinsic self-management, motivation, and cognitive control, which in turn benefit them in environments outside of the classroom setting such as the work office (Redding & Surr, 2017). Ultimately, this enables students to complete their programs with higher satisfaction rates, better grades, and increased confidence about next steps in their professional careers, and their ability to find a job with a significant wage increases (Kim & Baker, 2015;Lopez et al, 2017). Thus, CBE creates a learning environment that engages adult learners and prepares them for graduation and future educational and employment opportunities (Krauss, 2017).…”
Section: De S I G Ning For Equ It Ymentioning
confidence: 99%
See 1 more Smart Citation
“…Ȼ Some stakeholders may question the equitability of a cl approach. Cleary & Breathnach (2017), in their case study, argue that cl done well (i.e., based on an understanding of students and their needs) can support equity well.…”
Section: Benefits and Challenges Of CL In Teacher Educationmentioning
confidence: 99%